Bortezomib decreases the magnitude of a primary humoral immune response to transfused red blood cells in a murine model. Issue 1 (13th October 2016) - Natarajan, Prabitha; Liu, Jingchun; Santhanakrishnan, Manjula; Gibb, David R.; Slater, Lewis M.; Hendrickson, Jeanne E.
Abstract : BACKGROUND: Few therapeutic options currently exist to prevent or to mitigate transfusion‐associated red blood cell (RBC) alloimmunization. We hypothesized that bortezomib, a proteasome inhibitor currently being utilized for HLA alloantibody and ADAMTS13 autoantibody reduction, may be beneficial in a transfusion setting. Herein, we utilized a reductionist murine model to test our hypothesis that bortezomib would decrease RBC alloimmune responses. STUDY DESIGN AND METHODS: Wild‐type mice were treated with bortezomib or saline and transfused with murine RBCs expressing the human KEL glycoprotein. Levels of anti‐KEL immunoglobulins in transfusion recipients were measured by flow cytometry. The impact of bortezomib treatment on recipient plasma cells (PCs) and other immune cells was also assessed by flow cytometry and immunofluorescence. RESULTS: After bortezomib treatment, mice had a 50% reduction in splenic white blood cells and a targeted reduction in marrow PCs. Mice treated with bortezomib before the transfusion of KEL RBCs became alloimmunized in three of three experiments, although their serum anti‐KEL IgG levels were 2.6‐fold lower than those in untreated mice. Once a primary antibody response was established, bortezomib treatment did not prevent an anamnestic response from occurring. CONCLUSION: To the extent that these findings are generalizable to other RBC antigens and to humans, bortezomib monotherapy is unlikely to be of significant clinical benefit in a transfusion setting where complete prevention of alloimmunization is desirable. Given the impact on PCs, however, it remains plausible that bortezomib therapy may be beneficial for RBC alloimmunization prevention or mitigation if used in combination with other immunomodulatory therapies.